Peran Kyai dalam Membentuk Karakter Sosial Santri di Pondok Pesantren Al-Istiqomah Kebumen - Ryan Andrianto; Sri Haryanto; Salis Irvan Fuadi (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to: 1) Identify the social character of students at Al-Istiqomah Islamic Boarding School, Kebumen; 2) Examine the role of the kyai in shaping this character; and 3) Determine supporting and inhibiting factors. This qualitative field research used observation, interviews, and documentation for data collection. The results show that students’ social character is formed through religious activities such as studying classical texts, public speaking training, Al-Barzanji recitation, communal cleaning, group learning, and extracurriculars. The kyai plays a vital role through religious education, direct guidance, and exemplary behavior—like eating and drinking according to prophetic tradition, praying in congregation, and maintaining neighborly ties. Supporting factors include administrative staff, peer support, pesantren programs, and family encouragement. Hindering factors involve limited facilities, negative peer or social media influences, individualism, and students’ background. The kyai’s role remains central in building strong social character among students.